Thermally Reversible Polymeric Networks from Vegetable Oils - Yuliati, Frita (Polymers (Basel), 2020)
Low cross-link density thermally reversible networks were successfully synthesized from jatropha and sunflower oils. The oils were epoxidized and subsequently reacted with furfurylamine to attach furan groups onto the triglycerides, preferably at the epoxide sites rather than at the ester ones. Under the same reaction conditions, the modified jatropha oil retained the triglyceride structure more efficiently than its sunflower-based counterpart, i.e., the ester aminolysis reaction was less relevant for the jatropha oil. These furan-modified oils were then reacted with mixtures of aliphatic and aromatic bismaleimides, viz. 1,12-bismaleimido dodecane and 1,1′-(methylenedi-4,1-phenylene)bismaleimide, resulting in a series of polymers with T(g) ranging between 3.6 and 19.8 °C. Changes in the chemical structure and mechanical properties during recurrent thermal cycles suggested that the Diels–Alder and retro-Diels–Alder reactions occurred. However, the reversibility was reduced over the thermal cycles due to several possible causes. There are indications that the maleimide groups were homopolymerized and the Diels–Alder adducts were aromatized, leading to irreversibly cross-linked polymers. Two of the polymers were successfully applied as adhesives without modifications. This result demonstrates one of the potential applications of these polymers.